INVESTASI ASING LANGSUNG DAN PERTUMBUHAN EKONOMI DI WILAYAH ASEAN PERIODE 2004-2016 - Aditya Febriananta Putra; Suyanto .; Irzameingindra Putri Radjamin (Jurnal Ekonomi dan Bisnis, 2019)
Exertions to accelerate development carried out by developing countries in general are oriented towards improving or improving people’s lives. Developing countries are characterized as countries that lack capital, savings and investment. The role of Labor has a significant effect but has a negative impact on economic growth. Agriculture and Service also performance a significant role, despite having a positive impact on economic growth. While other variables, namely Fixed Capital Formation, Foreign Direct Investment, Export, Manufacture, and Fertility showed insignificant results on economic growth.